2021
DOI: 10.1093/rheumatology/keab725
|View full text |Cite
|
Sign up to set email alerts
|

Asporin regulated by miR-26b-5p mediates chondrocyte senescence and exacerbates osteoarthritis progression via TGF-β1/Smad2 pathway

Abstract: Objectives This study aimed to investigate the role and mechanism of asporin in modulating chondrocyte senescence in osteoarthritis (OA) pathology. Methods Asporin and senescence-related hallmark expression were examined in human and experimental OA mouse cartilage samples. Twelve-week-old male C57 mice were administered with recombinant protein (rm-asporin)- or asporin-siRNA-expressing lentiviruses via intra-articular inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…In our study, the immunostaining clearly demonstrated the high level of γH2AX in cartilage from DMM animals. Previous studies have shown that the level of γH2AX was increased in both DMM mice model and cartilage explants under irradiation and mitogenic stimulation 11,35 . These results together confirmed the presence of DNA damage in OA chondrocytes.…”
Section: Discussionsupporting
confidence: 81%
“…In our study, the immunostaining clearly demonstrated the high level of γH2AX in cartilage from DMM animals. Previous studies have shown that the level of γH2AX was increased in both DMM mice model and cartilage explants under irradiation and mitogenic stimulation 11,35 . These results together confirmed the presence of DNA damage in OA chondrocytes.…”
Section: Discussionsupporting
confidence: 81%
“…Our previous research has clarified that KO of MMP13 or Adamts5 gene in chondrocytes could significantly alleviate the OA-like phenotypes caused by the loss of TGF-β signaling, which concluded that both MMP-13 and Adamts-5 are critical downstream targets involved in TGF-β signaling pathways during cartilage homeostasis ( 10 , 35 ). In contrast, upregulation of TGF-β signaling in chondrocytes is able to suppress the production of MMP-13 and Adamts-5, which also functions as matrix-degrading enzymes ( 36 , 37 ). According to our data, with OA induction, the rates of chondrocytes positive for MMP-13 and Adamts-5 in KO mice were significantly lower than those in WT mice.…”
Section: Discussionmentioning
confidence: 98%
“…Another study showed that the decreased expression of miR-26b-5p during the pathogenesis of OA promoted the expression of Asporin. Asporin further regulated chondrocyte senescence and in destabilization of the medial meniscus (DDM)-induced joint degeneration by inhibiting the TGF-β1/Smad2 signaling pathway [ 45 ]. Although it has been confirmed that cartilage aging and OA progression are closely related to knee joint degeneration or osteoarthritis, it is rarely reported whether chondrocyte senescence is related to degeneration progression during facet joint degeneration.…”
Section: Discussionmentioning
confidence: 99%